FAKTOR-FAKTOR YANG MEMPENGARUHI KECURANGAN (FRAUD) DANA DESA DI KABUPATEN KEPULAUAN MERANTI: FACTORS AFFECTING FRAUD ON THE USE OF VILLAGE FUNDS IN MERANTI ISLANDS DISTRIC - Dede Kurniawan; Ria Nelly Sari; Alfiati Silfi (CURRENT: Jurnal Kajian Akuntansi dan Bisnis Terkini, 2023)
With individual morality serving as a moderating variable, the main of this research is to discover empiric evidence of the Effect of Competence, Appropriateness of Compensation, and Pressure on Fraud of Village Funds in the Meranti Islands Regency. The villages in Meranti Island district were the locations of this study. The method of sampling was a survey by sending out a questionnaire. The Statistical Package for the Social Sciences was used to process 206 of the 384 questionnaires that were distributed. Competence, appropriate compensation, and pressure all have an impact on village fund fraud in the Meranti Islands Regency, as shown by the study's findings. In the Meranti Islands Regency, individual morality can moderate the relationship between competence, appropriateness of compensation, and pressure associated with village fund fraud. The results of theoretical research suggest that competence plays a significant role in preventing fraud, as does the appropriateness of compensation. Specifically for village governments and other local governments in terms of reducing fraud.